Statistical Analysis of the Activities of Individual Entrepreneurs in the Regions of Russia - Vasilieva Angelica (SHS Web of Conferences, 2021)
The spread of coronavirus infection caused significant damage to enterprises in the region. The least protected business entities - individual entrepreneurs -suffered the most. The introduction of the self-isolation regime led to a decrease in demand for goods and services of individual entrepreneurs, an increase in business costs, and the accumulation of debts to landlords and creditors. Having fallen into a difficult economic situation, many individual entrepreneurs suffered losses and were forced to close their business. Once in a difficult situation, those entrepreneurs who were able to rebuild to work in the new economic conditions of restrictive measures survived. Some entrepreneurs began to master digital technologies and sell their goods using the Internet. Others switched to the production of antique products. Still others looked for buyers through popular social networks. Overcoming the economic crisis after the pandemic COVID-19 depends primarily on the activities of individual entrepreneurs in the region. It is they who quickly react and create jobs in the region, saturate markets with goods and services, and form the profitable part of the country’s budget. In connection with the above, it seems relevant to conduct a statistical analysis of the activities of individual entrepreneurs in the regions of Russia, in particular, to study the dynamics of individual entrepreneurs, their structure by types of economic activities, to determine the regions with the largest and smallest number of individual entrepreneurs per 1000 population, to identify the relationship between the number of individual entrepreneurs and their revenue from the sale of goods, work.